EFEK MEDIASI KEPUASAN KERJA TERHADAP KINERJA DENGAN KOMITMEN ORGANISASI, KOMUNIKASI INTERPERSONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIORS SEBAGAI VARIABEL ANTESEDEN - Ramdani Bayu Putra (Jurnal Praktik Bisnis, 2016)
This study aims to find and analyze the influence of organizational commitment, interpersonal communication and organizational citizenship behaviors to employee performance mediated by job satisfaction (Study: Employee Disaster Management Agency of West Sumatra Province).Population and sample of this research is all Employees Local Disaster Management Agency of West Sumatra province, amounting to a total of 52 people, with sampling techniques census method. While the model of the relationship between variables is Structural Equations Modeling (SEM) analysis tool used Smart PLS 2.0 M3.The study found there is a significant positive influence organizational commitment, interpersonal communication, organizational citizenship behaviors and job satisfaction on employee performance. Furthermore, there is also found a significant positive influence organizational commitment, interpersonal communication and organizational citizenship behaviors on job satisfaction. Other findings of this research also revealed that job satisfaction variables in this study reinforce the relationship or the influence of organizational commitment, interpersonal communication and organizational citizenship behaviors on employee performance. Keywords :    Organizational commitment, Interpersonal communication, Organizational citizenship behaviors, Job satisfaction and Employee performance.